The Effect Of MSG (Monosodium Glutamate) And Origin Of Stem Cutting On Growth Moringa Olifera (Moringa) Plant Seeds - Yususf, Mukhtar; Susanti, Rini (Jurnal Online Pertanian Tropik, 2020)
Moringa olifera is known worldwide as a nutritious plant and WHO has introduced Moringa as an alternative food to overcome nutritional problems (malnutrition). Moringa plants are sought after because they can be processed into a variety of herbal medicines to raw materials for skincare products. "Moringa seeds and leaves are in a trend to be used for processed skincare products because of the nutrients they contain. This research was conducted from March 2020 until June 2020 in the village of Sei Karang, Stabat Subdistrict, Langkat Regency using a factorial randomized block design with 2 levels of treatment ie without MSG (P0), 2 g / 5 liters of water (P1), 5 g / 5 liters of water (P2), 7 g / 5 liters of water (P3), and stem cuttings (W1), middle cuttings (W2) and tip cuttings (W3). The results showed that the treatment of cuttings in the middle (W1) showed the highest with a value of 9.67 on the observation of the number of shoots, while the interaction of MSG and the origin of cuttings showed a significant effect on the emergence of the highest treatment shoots at P1W1 (2.5 g / 5 liters of water and stem section) with a value of 12.67 days and observation of root length in the P2W2 treatment (5 g / 5 liters of water and the middle section) with a value of 10.67